Досвід використання добавки «Vita-Amarant» в якості адаптогену в аграрному секторі - Кіхаєва, Віола Юріївна; Kihaeva, Viola; Гончарова, Олена Вікторівна; Honcharova, Olena (My University, 2018)
Досліджено вплив біологічно активних речовин на організм страусів, якість біологічної продукції. Отриманні результати відображають позитивний вплив добавки «Vita-Amarant» на продуктивні показники страусів у ТОВ «Ясногородська страусова ферма». Встановлено, що використання амаранту в якості кормової добавки у страусівництві сприяє стимуляції катаболічних процесів, швидкості росту. Згодовування страусам на тлі загально-господарського раціону у встановленій оптимальній дозі добавки «Vita-Аmorant» сприяє поліпшенню загального функціонального стану організму страусів. Представлені дані експериментальних досліджень щодо використання одного зі способу підвищення якості кормів – введення в раціон нових речовин натурального походження з корисними властивостями. The influence of biologically active substances on the organism of ostriches, the quality of biological products. The obtained results reflect the positive influence of the supplement «Vita-Amarant» on productive indicators of ostriches on the farm «Yasnogorodskaya ostrich farm». It is obtained that the use of amaranth as a feed additive in ostrich farming promotes stimulation of catabolic processes, growth rate. Feeding ostriches against the backdrop of a ration in the farm in the prescribed optimal dose of the supplement «Vita-Amarant» contributes to the improvement of the general functional state of the organism of ostriches. The presented results of experimental studies on the use of one of the methods for improving the quality of feeds are introduction of new supplement of natural origin into the ration with useful properties.
Forming a financial mechanism the foreign trade of enterprises were investigated
Keywords: функціональний стан організму; functional state of the organism; добавка «Vita-Amarant»; ostriches, supplement «Vita-Amarant», amarant, rate of growth, functional state of the organism, productivity; амарант; amarant; швидкість росту; rate of growth; страуси; ostriches; продуктивність; productivity